Comparative efficacy of targeted therapy, chemotherapy and their combination for advanced cholangiocarcinoma: a systematic review and network meta-analysis - Liao, Zhoujun; Yao, Zhuoyue; Yang, Zhiqing; Yang, Shaohua; Gu, Wenjuan; Wang, Huijie; Deng, Lingyan (PeerJ, 2025)
Background Cholangiocarcinoma is a malignant tumor with a poor prognosis. Multiple randomized controlled trial (RCT) have shown conflicting benefits of different therapies. The study was to assess the effectiveness of chemotherapy (CT), targeted therapy (TT) and both of them (targeted therapy + chemotherapy; TT+CT) for advanced cholangiocarcinoma by a systematic review and network meta-analysis. Methods PubMed, EmBase, Medline, Cochrane were searched. Two reviewers independently selected published reports of RCT comparing any targeted therapy, chemotherapy and targeted therapy combined with chemotherapy vs. placebo. The outcomes were overall survival (OS) and progression-free survival (PFS) on the hazard ratio-scale (HR) and mean differences-scale (MD). Results We included 13 RCT involving 1,914 patients. We revealed a differential reporting of outcomes. All three treatments significantly reduced the HR in OS and PFS when compared with the placebo. HR and MD values of OS and PFS in TT+CT group were significantly better than those in the other two groups. Only targeted therapy can significantly improve PFS in patients. Conclusions 1) All treatments significantly reduced the hazard ratio in OS and PFS when compared with the placebo; 2) HR and MD values of OS and PFS in TT+CT group were significantly better; 3) Only targeted therapy alone significantly increased the PFS of patients, thereby improving the quality of life of patients.
Keywords: Systematic review; Comparative effectiveness review; Advanced cholangiocarcinoma; Chemotherapy; Targeted therapy